Genome characterization of three potyviruses affecting maize in Argentina - Trucco, Veronica Milagros; Cabrera Mederos, Dariel; Castellanos Collazo, Onias; Vaghi Medina, Carlos Gaston; Lenardon, Sergio Luis; Giolitti, Fabian (Wiley, 2023)
Argentina is globally recognized as both producer and exporter of maize, the most important cereal crop in the country. Several potyviruses affect the production of various crops, including maize. In this work, the complete nucleotide sequences of the RNA genome of three potyviruses, johnsongrass mosaic virus (JGMV), maize dwarf mosaic virus (MDMV) and sugarcane mosaic virus (SCMV), isolated from maize were obtained by next-generation sequencing (Illumina technology). The JGMV, MDMV and SCMV viral genomes were 9780, 9807 and 9729 nucleotides long, respectively. The polyprotein organization of each of potyvirus genome was determined; their sequences showed high values compared with polyprotein sequences of the other isolates reported worldwide (> 76.1% at the nucleotide sequence and > 85% at the amino acid sequence). The results of this work are the first data in Argentina of complete genome sequences of potyviruses obtained from maize and the first obtained for JGMV and MDMV.